Возрастная изменчивость бычковых рыб сем. Gobiidae - Билько, В.П.; Выборная, Л.И. (Вестник зоологии, 1972)
Age variability of plastic characters was studied in males and females of N. mela-nostomus Pall. and Mesogobius batrachocephalus P all. from the family Gobiidae in the Dnieper-Bug liman.